Unveiling the Impact of Problem-Based Learning on Students’ Science Process Skills and Cognitive Outcomes - Muttaqin Kurniawan; Lestariani, Nurlita; Lutvia Krismayanti (Bioeduca : Journal of Biology Education, 2025)
Problem-based learning (PBL) is an approach based on real-world problems that trains students to think scientifically, conduct investigations, and construct knowledge logically based on evidence. Through empirical experiences and complex problem-solving, students can improve their SPS and learning outcomes. This study aims: 1) to determine the effect of a PBL model on SPS and cognitive learning outcomes; 2) to determine the relationship between SPS and cognitive learning outcomes among students at MAN 1 West Lombok. This research method is a quantitative type of quasi-experimental research with a non-equivalent posttest control group design. The sample was 50 students in class X. The research instrument used observation sheets and tests. The data were analyzed using Manova and simple linear regression. Research has shown that PBL has a positive and significant effect on students’ SPS and cognitive learning outcomes. Furthermore, SPS play a mediating role between PBL and cognitive learning outcomes. PBL enhances students’ SPS, which in turn positively influence their learning outcomes